FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH PAREPARE - Suriana, Suriana; Hasdiana, Hasdiana (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this thesis is to determine the factors that influence the entrepreneurial motivation of students of the Faculty of Economics and Business, University of Muhammadiyah Parepare. This research uses a descriptive method. This research is descriptive. This research method consists of research objects, namely students of the Faculty of Economics and Business, University of Muhammadiyah Parepare, starting from December to February 2020. The analytical technique used in this study is to explain the factors that influence the motivation of students of the Faculty of Economics and Business, the University of Muhammadiyah Parepare. in entrepreneurship. The results of the study state that many dominant factors influence the motivation of students of the Faculty of Economics and Business, the University of Muhammadiyah Parepare in building entrepreneurship.